The Application of SLAM Technology in Indoor Navigation in Complex Indoor Environment - Yu, Changju (Transactions on Computer Science and Intelligent Systems Research, 2024)
This paper describes the application of SLAM in complex indoor environment. Through the joint work of sensor, LiDAR and visual camera, the real-time self-positioning and map construction are realized at the same time. However, in the practical application, there are also many challenges, the layout of the environment, the brightness of the environment, the presence of noise, the presence of dynamic objects and other environmental factors will lead to different degrees of data errors in SLAM technology. The small errors generated by a long time of work will gradually accumulate into potentially dangerous huge errors, and this is one of the biggest challenges for the current SLAM technology. Not only has that, the high configuration conditions required by SLAM technology also become one of the reasons why people do not choose it. However, the advantages of SLAM technology far outweigh the disadvantages. And almost all of these problems have corresponding solutions, SLAM technology is still very reliable, very widely used, the future of a great prospect of a technology.